Pendekatan STEM dalam Proyek Puding Labu Kuning untuk Menguatkan Kearifan Lokal Bahan Pangan - Marlina, Rina; Susilawati, Cica; Nuryantini, Ade Yeti; Agustina, Tri Wahyu; Julita, Ucu (INCARE, International Journal of Educational Resources, 2024)
The utilization of local food ingredients is often neglected in everyday life, even though it has great potential to strengthen local wisdom values among the community and increase student involvement in project-based learning activities. One of the local food ingredients that is rich in nutrients but underutilized is pumpkin, which is a good source of beta-carotene and fiber and has a great opportunity to be developed further. This study applied the STEM (Science, Technology, Engineering, and Mathematics) approach in the pumpkin pudding development project to strengthen local wisdom and increase the utilization of local food ingredients. The STEM approach was applied through several stages: first, from the science aspect, the nutritional composition of pumpkin was analyzed to maximize its health benefits; second, from the technology aspect, innovative processing techniques were used to optimize the taste and texture of the pudding; third, through engineering, recipe modifications were made to maintain product stability and increase durability; and fourth, mathematics was used in calculating the exact nutritional composition. The results showed that pumpkin pudding is not only of high nutritional value, but also well received by the public, especially teenagers. This project is expected to inspire the development of similar local food products that are not only delicious and nutritious, but also support local wisdom and food sustainability through an integrated STEM approach.